Effect of Filler Content on the Performance of Epoxy/PTW Composites - Mudradi Sudheer; Ravikantha Prabhu; Kandavalli Raju; Thirumaleshwara Bhat (Advances in Materials Science and Engineering)
This paper presents the mechanical and tribological characteristics of potassium titanate whisker (PTW) reinforced epoxy composites. The effect of various test variables and material parameters on the friction and wear behavior of epoxy/PTW composites has been studied systematically. Tribological tests were conducted on a pin-on-disc apparatus under dry sliding conditions. Addition of PTW was found to improve the wear resistance of the composites and 15 wt% PTW filled epoxy exhibited lowest specific wear rate and highest friction coefficient compared to other test samples. PTW additions showed beneficiary effect on density, hardness, and stiffness properties of composites; however, strength properties and ductility were found to decrease with the increasing content of PTW. Scanning electron microscope (SEM) images of tensile fractured surfaces and worn-out surfaces of selected samples revealed different fracture mechanisms.